A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group - Shavrin, Alexey V.; Smetana, Aleš (Zootaxa, 2018)
The fusculum-group of the genus Anthobium Leach, 1819 is defined and briefly discussed. It contains western-palaearctic A. fusculum (Erichson, 1839), with a new synonym Lathrimaeum mesasiaticum Kirschenblat, 1961 syn.n., and fourteen species from the eastern Palaearctic Region, nine of which are described as new: A. besucheti Shavrin & Smetana, sp.n. (central and eastern Nepal), A. capitale Shavrin & Smetana, sp.n. (China: Yunnan, Meili-Xue Shan), A. confucii Shavrin & Smetana, sp.n. (China: Sichuan, Gongga Shan and Erlang Shan; Hubei, Daba Shan), A. cuccodoroi Shavrin & Smetana, sp.n. (India: Uttar Pradesh), A.denticulatum Shavrin & Smetana, sp.n. (central Nepal), A. laozii Shavrin & Smetana, sp.n. (China: Yunnan, Diancang Shan, Yanmen), A. latissimum Shavrin & Smetana, sp.n. (China: Yunnan, Gaoligong Shan), A. liliputense sp.n. (China: Sichuan, Emei Shan) and A. splendidulum Shavrin & Smetana, sp.n. (China: Gaoligong Shan, Meili Xue Shan and Baima Shan). A key to the species of the fusculum group is given. Lectotypes are designated for Lathrimaeum cavicrus Champion, 1925 and L. monticola Cameron, 1924. Additionally, two Himalayan species of the nigrum group defined by Shavrin & Smetana (2017) are presented: A. alticola Coiffait, 1977 comb.nov. (from Deliphrum) and A. flaveolum Shavrin & Smetana, sp.n. (eastern Nepal). The key for the nigrum group was modified. All species are described/redescribed, illustrated and their geographical distribution is mapped. Several members of Anthobium are recorded for the first time from certain area: A. fusculum from Pakistan, A. altivagans (Cameron, 1941), A. cavicrus (Champion, 1925) and A. sociale (Cameron, 1941) from Nepal, and A. monticola (Cameron, 1924) from Pakistan and Nepal.